Suriname. Significant achievements 2010 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2022)
The main activities carried out by the Institute in Suriname during 2010 are identified, with respect to the needs and interests of the country, strengthening issues such as technology, trade, production, greenhouse, indoor agriculture, permaculture, composting, food safety, seedlings, export , agribusiness, export, biodigesters, natural resource management, watershed management. inclusion of women, control of pests, such as the fruit fly in carambolas and in the value chains of fruits, vegetables, cassava and ginger.